From library stacks to Library-in-a-Pocket : will users be around? - Choy, Fatt Cheong. (2011)
Purpose - As libraries move their focus from print collections to digital resources residing in the “cloud”, the library-user relationship has also changed dramatically. Power has clearly shifted from the library to the user and the dependence relationship has been inverted. The library-user relationship is a fundamental one and defines what libraries are, and therefore their future. It is therefore important to think about how to ensure that users continue to use and value libraries. The purpose of this article is to discuss the changing relationship between libraries and their users and to suggest critical factors to consider when designing and planning library services in order to sustain a viable library-user relationship.